The Implementation of the Food Quality Protection Act (FQPA) in Increasing the Safety Standards for New Pesticides Used on Foods - AlQahtani, Saad Nasser (Journal of Ecohumanism, 2024)
This paper examines the Food Quality Protection Act (FQPA) and its impact on enhancing safety standards for pesticides used on food in the United States. Initially, the study explores the Delaney Clause—a strict standard prohibiting carcinogenic food additives—which FQPA replaced with a more flexible "reasonable certainty of no harm" criterion. This shift allows the Environmental Protection Agency (EPA) to assess pesticide risk with consideration of potential benefits, even if a substance is carcinogenic at high doses. The paper also critiques the EPA’s implementation challenges, including reliance on quantitative risk assessment (QRA) and cumulative risk assessment, which quantify risks of multiple chemical exposures but face informational and regulatory limitations. Recommendations focus on refining judicial review and integrating cumulative risk assessment to strengthen the FQPA’s capacity to safeguard public health, especially for vulnerable populations such as children. This study underscores the importance of regulatory clarity and rigorous assessment methods in pesticide management.